Students’ perceptions on the implementation of ELT in a language center to their multicultural background - Amrih Bekti Utami (Universitas Negeri Yogyakarta, 2023)
This study is aimed at finding out the extent to which students’ perceptions towards the roles of language centers in higher education context clearly stated the implication of further better services and management of the language center. The study explores how students perceive the function of a language center in relation to their improvement of their language competence and performance. By using a set of well-developed questionnaires, researchers conducted the study and collected the data from 303 participants of higher education students with multicultural background. The results demonstrate that a language center in a higher education context need to provide diversification as well as standardization, particularly, on language services offered to all of university stakeholders, especially, the students taking parts as active users of the language center. The reported results have shown a special role of a language center and the opportunity of further language policy maker in a university level to illuminate the roles of the language center as an intermediatory between students and academic language services.